2017
DOI: 10.1186/s12957-017-1121-8
|View full text |Cite
|
Sign up to set email alerts
|

ALPPS (associating liver partition and portal vein ligation for staged hepatectomy) does not affect proliferation, apoptosis, or angiogenesis as compared to standard liver resection for colorectal liver metastases

Abstract: BackgroundALPPS (associating liver partition and portal vein ligation for staged hepatectomy) is a novel two-stage strategy to induce rapid hypertrophy of the future liver remnant (FLR) when patients are in danger of postoperative liver failure due to insufficient FLR. However, the effects of ALPPS on colorectal liver metastases (CRLM) are not clear so far. The aim of our study was to determine whether ALPPS induces proliferation, apoptosis, or vascularization compared to standard (one-stage) liver resection.M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…CRLM confers the best clinical outcomes; a series by Hernandez-Alejandro involving 14 patients who underwent ALPPS for planned liver resection of CRLM demonstrated low morbidity (14% Clavien-Dindo ≥ Grade IIIB) and no mortality (23). In addition, a recent study by Joechle et al has demonstrated that there is no difference between ALPPS and standard liver resection on tumour cell proliferation, apoptosis and vascularization in CRLM (18).…”
Section: Guide On Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRLM confers the best clinical outcomes; a series by Hernandez-Alejandro involving 14 patients who underwent ALPPS for planned liver resection of CRLM demonstrated low morbidity (14% Clavien-Dindo ≥ Grade IIIB) and no mortality (23). In addition, a recent study by Joechle et al has demonstrated that there is no difference between ALPPS and standard liver resection on tumour cell proliferation, apoptosis and vascularization in CRLM (18).…”
Section: Guide On Patient Selectionmentioning
confidence: 99%
“…Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS) is a novel two-staged procedure which aims to induce rapid hypertrophy of the FLR (18,19). ALPPS was first formally reported in a poster presentation by de Santibañes et al in 2011 (20), and subsequently described in a landmark study involving 25 patients by Schnitzbauer et al in 2012 (21).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, data regarding proliferation indices (Ki67 index) are contradictory in literature. While Fukami et al [55] found an increase in Ki67 from 60 to 80% between step 1 and 2 in ALPPS, Joechle et al[56]. did not reveal any difference in Ki67 between ALPPS or conventional hepatectomy…”
mentioning
confidence: 98%
“…Tanaka et al[8] compared Ki67 expression in both approaches showing significantly induced of Ki67 index in PVE but not ALPPS patients. Joechle et al[20] concluded that markers of tumor proliferation and angiogenesis were similar among patients undergoing ALPPS and standard liver resection.…”
Section: Alpps: Better Than Two-stage Hepatectomy?mentioning
confidence: 99%